2020
DOI: 10.1186/s12879-020-05507-4
|View full text |Cite|
|
Sign up to set email alerts
|

The use of intravenous immunoglobulin gamma for the treatment of severe coronavirus disease 2019: a randomized placebo-controlled double-blind clinical trial

Abstract: Background Coronavirus disease 2019 (COVID-19) has infected people in many countries worldwide. Discovering an effective treatment for this disease, particularly in severe cases, has become the subject of intense scientific investigation. Therefore, the objective of this study was to evaluate the efficacy of intravenous immunoglobulin (IVIg) in patients with severe COVID-19 infection. Methods This study was conducted as a randomized placebo-controlled double-blind clinical trial. Fifty-nine patients with sev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
159
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(165 citation statements)
references
References 26 publications
1
159
0
5
Order By: Relevance
“…IVIg has been effectively used in some COVID-19 patients including COVID-19- immune inflammatory syndrome resembling Kawasaki's disease ( 10 ) but whether the antibodies detected in the present study have any protective or therapeutic effects in COVID-19-exposed populations is uncertain. A recent randomized placebo-controlled double-blind clinical trial with IVIg in severe COVID-19-infected patients showed that the in-hospital mortality rate was significantly lower in the IVIg group compared to the control group ( 11 ). Considering that acquired immunity may be short-lived in persons with mild or asymptomatic COVID-19 infection ( 12 ), the IVIg administrations currently prescribed as monthly maintenance for patients with immunodeficiency and immune-mediated diseases ( 6 ), may theoretically provide some added benefit, even though these natural or cross-reactive antibodies are not affinity maturated for SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…IVIg has been effectively used in some COVID-19 patients including COVID-19- immune inflammatory syndrome resembling Kawasaki's disease ( 10 ) but whether the antibodies detected in the present study have any protective or therapeutic effects in COVID-19-exposed populations is uncertain. A recent randomized placebo-controlled double-blind clinical trial with IVIg in severe COVID-19-infected patients showed that the in-hospital mortality rate was significantly lower in the IVIg group compared to the control group ( 11 ). Considering that acquired immunity may be short-lived in persons with mild or asymptomatic COVID-19 infection ( 12 ), the IVIg administrations currently prescribed as monthly maintenance for patients with immunodeficiency and immune-mediated diseases ( 6 ), may theoretically provide some added benefit, even though these natural or cross-reactive antibodies are not affinity maturated for SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] No differences on mortality or in the need of IMV were observed in patients treated with ruxolitinib, 36 while IVIg reduced mortality in hospitalised patients requiring NIMV/IMV. 39 The addition of colchicine to SOC allowed a larger number of patients to achieve cumulative event-free 10-day survival, using a composite outcome including mortality or need of IMV, and a lower number of patients displayed clinical deterioration. 38 However, patients with a slightly milder phenotype not requiring IMV were enrolled.…”
Section: Other Immunomodulatory Drugs Efficacymentioning
confidence: 99%
“…IVIG products represent another potential antibody treatment as these products exhibit cross-reactivities and neutralizing capabilities to SARS-CoV-2 (Diez et al, 2020a;Diez et al, 2020b). Several studies reported clinical efficacies of IVIG infusion to treat severe and critically ill COVID-19 patients (Cao et al, 2020;Gharebaghi et al, 2020;Shao et al, 2020). In one study, three severe COVID-19 patients receiving high-dose IVIG daily for 5 days had clinical improvement (Cao et al, 2020).…”
Section: Convalescent Plasma and Ivig Treatment Of Covid-19 Patientsmentioning
confidence: 99%
“…This study suggests that early treatment of COVID-19 patients within 7 days after admission with a high dose (>15 g d -1 ) is beneficial and may be an effective treatment strategy. Furthermore, in a randomized placebo-controlled double-blind clinical trial, 59 patients with severe COVID-19 who did not respond to initial treatment were treated with IVIG or placebo (Gharebaghi et al, 2020). The IVIG-treated patients had a significantly lower mortality rate (20.0% vs. 48.3%), indicating that IVIG administration in this group of patients improves clinical outcome.…”
Section: Convalescent Plasma and Ivig Treatment Of Covid-19 Patientsmentioning
confidence: 99%